α - to - β transformation on PVDF films obtained by uniaxial stretch - Sencadas, Vítor João Gomes Silva (2006)
The α to β phase transformation of PVDF through the stretching process at different temperatures was investigated. The optimum stretching conditions were studied and characterised by infrared spectroscopy and differential scanning calorimetry. The maximum β−phase content was achieved at 80ºC and a stretch ratio of 5. Accompanying the phase transformation, a orientation of the polymer chains and a packing of the crystalline structure is observed. The stretch ratio does not significantly affect the degree of crystallinity.